Diminished brain 5-HT transporter binding in major depression: a positron emission tomography study with [11C]DASB. - Selvaraj, S; Murthy, N; Bhagwagar, Z; Bose, S; Hinz, R; Grasby, P; Cowen, P (2011)
BACKGROUND: The serotonin transporter (5-HTT) plays a critical role in the regulation of serotonin neurotransmission and has been implicated in the pathophysiology of major depression. In a previous positron emission tomography study, we found no difference in brain 5-HTT binding between unmedicated recovered depressed patients and healthy controls. AIM: This study aims to assess brain 5-HTT binding in a group of unmedicated acutely depressed patients in comparison to healthy controls. METHODS: We studied 5-HTT binding using [(11)C]DASB in conjunction with positron emission tomography in 12 medication-free depressed patients with a mean duration of illness of about 1 year and 24 healthy controls. RESULTS: The depressed patients had lowered 5-HTT binding in several brain regions including brain stem, thalamus, caudate, putamen, anterior cingulate cortex and frontal cortex. CONCLUSIONS: These results suggest that diminished availability of the 5-HTT in the brain may be a state marker of acute depression. Alternatively, low 5-HTT binding may delineate a group of depressed patients with a poor long-term prognosis.